Preferensi perilaku membolos dan alternatif pemecahannya pada siswa SMK Humaniora Kerinci - Rilla Gina Gunawan; Mukhaiyar Mukhaiyar; Azwar Ananda (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
Teachers play a role in the process of transferring knowledge effectively so that their students learn the material in a way that is conducive to the desired outcome. Successful and efficient processes, actions, ways of nurturing, efforts, actions, and activities that provide positive results are the essence of coaching. The purpose of this study was to identify the causes of truant behavior in grade XI students at SMK Humaniora Kerinci as well as potential solutions to the problem. This research is quantitative descriptive research. The subjects of this study were class XI BD students who skipped class. Data collection was conducted through interviews, observations, and document studies. Data were analyzed by reducing data, displaying data, and drawing conclusions. The research findings suggest that BD's slow learning rate is a contributing factor to their low self-esteem and inability to adapt, both of which play a role in their tendency to engage in risky behavior when dealing with friends. Negative perceptions of the subjects' difficulties may stem from outside influences such as peer groups known to misbehave, instructors with limited capacity to accommodate diverse learning styles, r inappropriate methods of delivering course materials. An alternative suggestion is for BD to be enrolled in a school that accepts inclusive school students. Strategies for introducing catch-up lessons to customize their lessons to each student, teachers must first investigate their differences. Teachers should consider students' skill levels when setting learning objectives. For example, give BD fewer tasks or lighter tasks than his peers